Intrastriatal injection of alpha-synuclein preformed fibrils to rats results in L-DOPA reversible sensorimotor impairments and alterations in non-motor function - Fleming, Sheila M.; Scott, Sophia; Hamad, Edward J.; Herman, Danielle E.; Holden, John G.; Yan, Lily; Linning-Duffy, Katrina; Kemp, Christopher J.; Patterson, Joseph R.; Miller, Kathryn M.; Kubik, Michael; Kuhn, Nathan; et al. (Frontiers in Neuroscience, 2025)
IntroductionThe alpha-synuclein (α-syn) preformed fibril (PFF) model of Parkinson’s disease (PD) is widely used in rodents to understand the mechanisms contributing to progression of pathology and neurodegeneration in the disorder. While the time course of pathology in the α-syn PFF rat model has been well characterized, it has been more challenging to determine reliable and reproducible behavior impairments. This is mainly due to α-syn PFF injections resulting in a partial nigrostriatal lesion that make motor anomalies more subtle and difficult to detect, just as in patients with PD. In the present study we sought to examine the effect of increased striatal distribution and injection quantity of α-syn PFFs in rats on accumulation of phosphorylated α-syn inclusions, nigrostriatal degeneration, sensorimotor behavior, and nonmotor function related to PD.MethodsMale Fischer 344 rats were injected unilaterally in the striatum with a total of 24μg α-syn PFFs distributed into three sites, or an equal volume of phosphate buffered saline (PBS) as a control condition. Sensorimotor function was assessed using a battery of behavioral tests sensitive to varying degrees of nigrostriatal neurodegeneration. Non-motor testing included assays for olfaction, emotional reactivity, cognitive function, and sleep.ResultsAt six months post injection, α-syn PFF rats displayed significant movement and somatosensory asymmetries compared with control rats. Time to initiate a forelimb step and time to contact an adhesive stimulus on the forepaw took significantly longer with the contralateral limb compared with the ipsilateral limb in α-syn PFF rats. Further, hindlimb stepping in the cylinder was significantly reduced in α-syn PFF-injected rats compared with controls. Cognitive function was also affected in the α-syn PFF rats, with investigation time significantly decreased in an object recognition test. Levodopa reversibility was observed in the movement initiation and cylinder tests. Postmortem analysis revealed a 55% loss of nigral tyrosine hydroxylase immunoreactive neurons and a 63% reduction in striatal dopamine content in α-syn PFF-injected rats.ConclusionThus, using the present α-syn PFF surgical parameters, sufficient nigrostriatal degeneration can be achieved to manifest significant motor and non-motor deficits. These rat α-syn PFF surgical parameters will be important for preclinical assessment of novel diseasemodifying therapies.